2019
DOI: 10.1177/2055207618821521
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring in the digital era: Stimulating dialogues on health topics in collaboration with social media influencers

Abstract: In today’s media landscape, audiences increasingly turn to online communities for media consumption and to exchange information about specific niche interests such as health-related topics. This calls for a segmented approach in which interventions are targeted at online communities, tailored to their specific cultures and health-related perceptions, and leverage the dynamics of conversation and social influence in online networks. Strategies drawn from the field of influencer marketing provide interesting opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 49 publications
(62 reference statements)
3
72
0
Order By: Relevance
“…For over a decade, the marketing sector has used social media influencers as a cost efficient and effective way to sell products [23]. Social media influencers are just starting to be used in public health, with research beginning to show their promise in promoting various health behaviors; social media influencers have shown promise in achieving high levels of digital engagement and positive health outcomes, with researchers calling for more investigation into applications of this model for other behaviors [24][25][26][27]. The present study applies these theories to a campaign that promotes positive views of the flu vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, the marketing sector has used social media influencers as a cost efficient and effective way to sell products [23]. Social media influencers are just starting to be used in public health, with research beginning to show their promise in promoting various health behaviors; social media influencers have shown promise in achieving high levels of digital engagement and positive health outcomes, with researchers calling for more investigation into applications of this model for other behaviors [24][25][26][27]. The present study applies these theories to a campaign that promotes positive views of the flu vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of user-generated content is well established and recognized in different sectors. Industries such as fashion, tourism and beauty have already picked up on the importance and the impact of user generated content, exploiting and taking advantage of its impact and convenience for firms, brands and marketers (Lutkenhaus et al, 2019;Zhou et al, 2019). Staff (2018) even claims that people trust influencers more than they trust a brand and, additionally, a report by Nielsen (2015) revealed that about 83% of people completely or somewhat trust the recommendations of friends and family, and about 66% trust consumer opinions posted online.…”
Section: User-generated Content In Healthcarementioning
confidence: 99%
“…At the beginning of the 21st century, when the WWW was spreading, information provided by a personal doctor on the web and by medical universities and government sites became the most trusted sources of online health information (Dutta-Bergman, 2003). In today's media landscape, patients are turning to the Internet also to search for peer-to-peer recommendations (Lutkenhaus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, expert health organisations could consider forging alliances with social media influencers and key opinion leaders, to run targeted health promotion campaigns. Lutkenhaus et al 16 recently demonstrated, using network and content analysis of tweets related to vaccine hesitancy in the Netherlands, that it is possible to identify online communities with specific health perceptions and identify social media influencers as potential collaboration partners within the vaccination network. The authors suggest that ‘health communication professionals and social influencers can collaborate effectively to create health interventions that are tailored to the preferences, perceptions and cultures of these online communities’ 16.…”
Section: ​Social Media Campaignsmentioning
confidence: 99%